Properties of particleboard made from kenaf (Hibiscus cannabinus L.) as function of particle geometry - A. H., Juliana; M. T., Paridah; S., Rahim; I., Nor Azowa; U. M. K., Anwar (Elsevier, 2011)
An examination of particle geometry was carried out after the kenaf stems were chipped and flaked and the identified geometry was compared with that of rubberwood. The particle geometries were then classified into several classes; 10 for kenaf core, 7 for kenaf bast, and 7 for rubberwood. The results indicate that most of kenaf core particles were of rectangular or nearly rectangular shapes whilst kenaf bast was in the form of curl and kneel form. Overall, board made from a combination of 70% rubberwood (RW) and 30% kenaf (K) was characterized by greater strength and stability than boards comprising 100% kenaf. These results provide enough evidence that combining rubberwood with kenaf particles imparts better mechanical and physical properties of the admixture RW–K board. Nonetheless, segregation of kenaf core and kenaf bast is necessary since both materials produced different particle geometries thus require different processing parameters. Between the two, kenaf core has better compatibility with rubberwood and shows superior performance than kenaf bast.